Categories are in flux, but their computational representations are fixed: That's a problem. Issue 2 (2nd January 2020) - Gupta, Prashant; Gahegan, Mark
Abstract: As research advances, our conceptual understanding also changes. Computational approaches do little to recognize the evolution that occurs at the conceptual level during the research process. This can result in misunderstanding between knowledge producers and consumers and so inhibit the reusability of outcomes. In this article, we describe how changes at the conceptual level can be represented, along with related changes to data and methods, and how appropriate connections between these various artefacts can be maintained. To demonstrate these ideas, we show how categories used in remote sensing and land cover analysis change over time and how these changes are linked to various research activities. We present a new system (called AdvoCate ) that augments typical GIS and remote sensing functionality with a conceptual model of categories that can undergo change, and that also captures the cause of conceptual change and its extent. We argue that concepts and categories should be represented explicitly and richly within GIS, because without this, we have a poor idea of what our modeled entities really mean, and by implication how they should be used appropriately. We demonstrate the usefulness of this deeper representation using examples of category evolution from a land cover mapping exercise.